Assessing Investment Allocation Funds on the Growth of Total Assets Among Islamic Insurance Firms in Indonesia - Tafitri, Ulviya; Jazil, Thuba (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The objective of this research is to examine the impact of Islamic insurance funds' asset allocation, which includes mudharabah deposits, sovereign sukuk, corporate sukuk, and Islamic mutual funds, on the asset growth of Islamic insurance funds in Indonesia. This study employs quantitative methodology, utilizing Vector Autoregression (VAR) and Ordinary Least Square (OLS) to analyze data series spanning from January 2016 to April 2023. The findings of the ordinary least squares (OLS) analysis indicate that the proportion of funds invested in Islamic mutual funds, government sukuk, corporate sukuk, and mudharabah deposits has a substantial and positive impact on the expansion of Islamic insurance assets. Moreover, the findings from the VAR indicate that a positive and statistically significant short-term relationship exists exclusively with government sukuk and its impact on the expansion of Islamic insurance assets. To optimize the allocation of investment funds for investors and stakeholders, sovereign sukuk and corporate sukuk may be considered, in light of the Impulse Response Function and Variance Decomposition analysis.